From Cato to Plato and Back Again: Friendship and Patronage in John Tzetzes’ Letters and Chiliades - Lovato, Valeria F. (Classica et Mediaevalia, 2021)
In many passages of his works, John Tzetzes likens himself to different figures from the Greek and Roman past in order to emphasise relevant features of his authorial persona. This strategy has been the subject of recent studies, which underscore the self-advertising agenda underlying Tzetzes’ constant reference to – and identification with – Greek and Roman models. Drawing on and going beyond this strand of literature, this paper pursues two main goals. First, it aims to situate Tzetzes’ references to these figures from the past within the broader sociocultural dynamics informing his self-fashioning strategy. To this end, it will focus on passages of his works dealing with friendship and patronage, two social practices that were crucial to any Byzantine writer. Second, the paper seeks to show that Tzetzes uses these figures to reflect upon his condition as a commissioned writer, skilfully employing them to create an authorial narrative that both spells out and plays with the constraints and contradictions stemming from his professional status.